A comparative study of the thermo-mechanical properties of polylactide/cellulose nanocrystal nanocomposites obtained by two surface compatibilization strategies. (December 2021) - Faraj, Hajar; Sollogoub, Cyrille; Guinault, Alain; Gervais, Matthieu; Bras, Julien; Salmi-Mani, Hanène; Roger, Philippe; Le Gars, Manon; Domenek, Sandra
Abstract: Nanocomposites of poly(lactide) (PLA) and cellulose nanocrystal (CNC) were fabricated using two different types of covalently grafted surface compatibilizers, namely fatty acids (lauric or stearic acid) and poly(glycidyl methacrylate) (PGMA) bearing reactive epoxy end-groups. Temperature-Modulated DSC analysis informed on weak attractive interaction of PLA and CNC-g-lauric acid and weak plasticizing of CNC-g-stearic acid. Despite that a homogenous dispersion of up to 50 wt% of CNC in PLA was obtained and the rubbery elastic moduli increased 150-fold as compared to PLA. CNC-g-PGMA phase-separated in PLA but partially to it at the interface. It yielded a 40-fold increase of rubbery plateau moduli. The data analysis with the Ouali model for percolated systems and the Halpin-Tsai model for composites with short fibers showed that CNC-g-lauric acid percolated in PLA. However the effective modulus of the percolated network was smaller than that of unmodified CNC. Reactive compatibilization of PLA with CNC-g-PGMA prevented percolation but lead to high filler/matrix coupling. In that case, the modulus increase could be described using the Halpin-Tsai model. In conclusion, surface compatibilizing even if developing only weak interactions with the polymer matrix helps to obtain homogenous nanocomposites, but the strength of the percolated network is lowered because it weakens also the CNC/CNC interactions. Reactive surface compatibilizing using polymers can be an interesting alternative, but needs to be optimized to take advantage of the high filler/matrix coupling and avoid phase separation. Highlights: Surface esterification of cellulose nanocrystals allows homogenous dispersion up to 50 wt% in a polylactide matrix. Surface grafts being or not reactive with polylactide increase the mechanical percolation threshold of cellulose nanocrystals. Even weak surface interactions between cellulose nanocrystals and polylactide increase the rubbery modulus 150-fold.